LEARNING STYLES AND PERSONALITY AS FACTORS AFFECTING ACADEMIC PERFORMANCE AMONG STUDENTS OF DIFFERENT ETHNICITY: A CASE STUDY - Bokhari, Mohamad (Journal of Human Capital Development (JHCD), 2011)
Learning styles and personality are among the factors given the limelight when students’ academic execellence is discussed. Personality, a psychophysical system within an individual which determines an individual’s behaviour, character and way of thinking also plays a part in students’ academic performance. The actual problem among students is their unwillingness to strive their fullest to achieve academic excellence, which stems from the absence of a clear-cut aim of living. Aims must be specific, clear, properly planned and supported with action. This research is significant to raise the awareness that learning styles is not the most prominent factor in determining students’ academic achievement. Descriptive frequency and descriptive inferencing methods were used in this research. Results from the research show that students who ‘always ask for assistance from my teachers (lecturers) and classmates’ will score excellently in UPSR, PMR or in the university - Universiti Teknikal Malaysia Melaka (UTeM). Keywords: learning styles, personality, academic execellence